Transforming food systems to deliver nutritious foods: The vital roles of fortification and biofortification - Mkambula, Penjani; Birol, Ekin; Friesen, Valerie M.; Munyua, Hilda M.; Alberts, Daniel; Aytekin, Destan; Mudyahoto, Bho; Boy, Erick; Mbuya, Mduduzi N. N. (Global Alliance for Improved Nutrition, 2022)
An estimated 2 billion people globally are affected by micronutrient deficiencies, while around one third of the global population is at risk of at least one micronutrient deficiency. Micronutrient deficiencies, also known as hidden hunger, can be linked to significant disease burden and economic loss. Food-based approaches to tackling micronutrient deficiencies include improving the micronutrient content of widely consumed foods through large-scale food fortification or biofortification, both of which have been proven to be efficacious, cost-effective, and scalable in increasing micronutrient intakes and improving associated biological outcomes. The literature is replete with evidence on the efficacy, acceptability, and cost-effectiveness of each of these approaches but with few discussions of their complementarity. In this paper, we present a narrative review of food fortification and biofortification and highlight their complementary roles in helping transform food systems to deliver healthy and accessible foods for all.